The visual basis of reading and reading difficulties - Stein, John (Frontiers in Neuroscience, 2022)
Most of our knowledge about the neural networks mediating reading has derived from studies of developmental dyslexia. For much of the 20th C. this was diagnosed on the basis of finding a discrepancy between children’s unexpectedly low reading and spelling scores compared with their normal or high oral and nonverbal reasoning ability. This discrepancy criterion has now been replaced by the claim that the main feature of dyslexia is a phonological deficit. It is now argued that we should test for this to identify dyslexia. However, grasping the phonological principle is essential for all learning to read; so every poor reader will show a phonological deficit. The phonological theory does not explain why dyslexic people, in particular, fail; so this phonological criterion makes it impossible to distinguish developmental dyslexia from any of the many other causes of reading failure. Currently therefore, there is no agreement about precisely how we should identify it. Yet, if we understood the specific neural pathways that underlie failure to acquire phonological skills specifically in people with dyslexia, we should be able to develop reliable means of identifying it. An important cause in people with dyslexia is probably impaired development of the brain’s rapid visual temporal processing systems; these are required for sequencing the order of the letters in a word accurately. Such temporal, ‘transient’, processing is probably carried out primarily by a distinct set of ‘magnocellular’ (M-) neurones in the visual system; and the development of these has been found to be impaired in most people with dyslexia. Therefore, assessing poor readers’ visual temporal processing skills should enable dyslexia to be reliably distinguished from other causes of reading failure and this will suggest principled ways of helping these children to learn to read, such as magnocellular training, yellow or blue filters or omega 3 fatty acid supplements. This will enable us to diagnose developmental dyslexia with confidence, and thus to develop educational plans targeted to exploit each individual child’s strengths and compensate for his weaknesses.